Financial statement analysis and security valuation - Penman, Stephen H. (New York : McGraw-Hill Irwin, 2013)
Shows students how to extract information from financial statements and use that data to value firms. This title also shows how to handle the accounting in financial statements and use the financial statements as a lens to view a business and assess the value it generates
1. Financial statements and valuation -- 2. The analysis of financial statements -- 3. Forecasting and valuation analysis -- 4. Accounting analysis and valuation -- 5. The analysis of risk and return
Includes index
Keywords: Financial statements